PRAGMATIC STRATEGIES IN ENGLISH MEDIA DISCOURSE: A COMPARATIVE ANALYSIS OF ONLINE AND PRINT NEWS - Bekberganova , Khilola; Nazarov, Murod (THE PLACE AND ROLE OF TURKEY AND THE NEAR REGION IN THE PROCESSES OF SCIENTIFIC, SOCIAL, AND CULTURAL DEVELOPMENT, 2025)
This study explores the pragmatic strategies employed in English media discourse through a comparative analysis of online and print news formats. Pragmatics, encompassing implicature, speech acts, presupposition, and deixis, plays a crucial role in how media constructs meaning, engages audiences, and influences perceptions. The research highlights the evolution from traditional print media, which prioritizes concise, authoritative narratives with inferential strategies, to dynamic online platforms that leverage interactivity, hypertextuality, and sensationalism to drive engagement. Drawing on real sources indexed in high-level databases such as ResearchGate, Macrothink Institute, and others, the analysis reveals medium-specific adaptations: print headlines often use presupposition and nominalization for objectivity, while online versions flout Gricean maxims to create clickbait, amplifying virality but risking misinformation. The relevance of this work lies in addressing gaps in discourse analysis amid information overload and fake news, informing media literacy, journalistic practices, and pragmatic theory. The purpose is to delineate how these strategies adapt to technological affordances, evaluate their impact on audience interpretation, and propose hybrid models for ethical communication. Methodologically, it employs Critical Discourse Analysis (CDA) and functional-pragmatic frameworks on corpora from outlets like The Times and CNN, incorporating cross-cultural perspectives from British, Malaysian, and Baluchistan newspapers.